The scarlet letter - Hawthorne, Nathaniel, 1804-1864 (Oxford world's classics (Oxford University Press), 2007)
After a two-year absence a husband returns to find his wife wearing the scarlet 'A' for Adulteress on her breast. Determined to find her lover, he embarks on a destructive path of revenge. This edition uses the most authoritative text, with a wide-ranging critical introduction. - ;'Thou and thine, Hester Prynne, belong to me.'. With these chilling words a husband claims his wife after a two-year absence. But the child she clutches is not his, and Hester must wear a scarlet 'A' upon her breast, the sin of adultery visible to all. Under an assumed name her husband begins his search for her lover.